Evidence of the Storegga Tsunami 8200 BP? An Archaeological Review of Impact After a Large-Scale Marine Event in Mesolithic Northern Europe - Nyland, Astrid J.; Walker, James; Warren, Graeme (Frontiers in Earth Science, 2021)
Around 8200 years ago, the Storegga tsunami hit the coasts of the Norwegian and North Seas. This event is well known from wide ranging geological and palaeobotanical work undertaken over the last 30 years. Outside of attempts at palaeodemographic models, however, exploration of the social impact of the wave on Mesolithic hunter-gatherer societies living on the coasts of west Norway, the north and east British Isles, and around the southern North Sea basin have been less common. It has been widely assumed that the tsunami was a disaster – but what constituted a disaster for the Mesolithic peoples who lived through this event? What can we learn about life after natural hazards by considering the archaeological material from regions with distinct Mesolithic histories? This paper presents a review of evidence of the Storegga tsunami at Mesolithic sites from western Norway, the Northeast UK, and elsewhere around the southern North Sea basin. We consider the ways in which the social impact of the Storegga tsunami has been studied up till now and suggest an alternative way forward.